METHODS OF STUDYING CHARACTERISTICS OF PERSONALITY AND INTERPERSONAL RELATIONSHIPS OF PRESCHOOL CHILDREN WITH MENTAL DISABILITY - Nabiyev son of Ravshanjon Shavkatjon; Erkinov son of Javohir Mirzahid (Galaxy International Interdisciplinary Research Journal, 2023)
This article highlights the study of the personality and interpersonal relationships of preschool children with mental retardation through various methods. Scientific evidence and methods are thoroughly covered by scientists.